Instrumental Neutron Activation Analysis (INAA) As-sessment of REE of Soil from Mining Site Umuahia, Abia State, South East, Nigeria - M. E. Onudibia; P. S. C. Silva; A.A. Essiett; G. S. Zahn; F. A. Genezini; H. M. S. M. D Linhares; N. C. Nnamani; M. C. Bede; F. O. Okoh; E. E. Imeh; C. M. Odoh (Brazilian Journal of Radiation Sciences)
In this work, the main goal was to examine the REE concentration and distribution pattern in soil from Umuahia, Abia State, Southeast, Nigeria, in a clay mining site compared with a non-contaminated site approximately 3 km away. The REE were determined by Instrumental Neutron Activation Analysis (INAA) at IPEN, Brazil. The main mineralogy of the samples was determined by XRD. The following REE were determined: Ce, Eu, La, Lu, Nd, Sm, Tb and Yb. Soil samples from the mining area present quartz and kaolinite as their main constituents, with REE concentrations comparable with that of the Upper Continental Crust and the North American Shale Composite. The calculated Geoaccumulation index (IGeo) indicate that REE have natural origin and ∑LREEN/∑HREEN ratio show an enrichment of the light over heavy REE, in samples of the clay mining area.